Fate of graft cells: what should be clarified for development of mesenchymal stem cell therapy for ischemic stroke? - Ikegame, Yuka; Yamashita, Kentaro; Nakashima, Shigeru; Nomura, Yuichi; Yonezawa, Shingo; Asano, Yoshitaka; Shinoda, Jun; Hara, Hideaki; Iwama, Toru (Frontiers in Cellular Neuroscience, 2014)
Mesenchymal stem cells (MSCs) are believed to be promising for cell administration therapy after ischemic stroke. Because of their advantageous characteristics, such as ability of differentiation into neurovascular lineages, avoidance of immunological problems, and abundance of graft cells in mesodermal tissues, the number of studies regarding MSC therapy have increased recently. However, several controversies are yet to be resolved before a worldwide consensus regarding a standard protocol is obtained. In particular, the neuroprotective effects, the rate of cell migration to the lesion, and differentiation direction differ depending on preclinical observations. Analyses of these differences and application of recent developments in stem cell biology or engineering may contribute to identification of criteria for optimal stem cell therapy in which reliable protocols, which control cell quality and include safe administration procedures, are defined for each recovery phase after cerebral ischemia. In this mini review, we examine controversies regarding the fate of grafts and the prospects for advanced therapy that could be obtained through recent developments in stem cell research.